Parental Efficacy and Role Responsibility for Assisting in Child's Healthful Behaviors. (September 2014) - Ice, Christa L.; Neal, William A.; Cottrell, Lesley
The epidemic of childhood obesity, and its subsequent impact on negative health outcomes, continues to plague the United States. Better health outcomes have been linked to increased child achievement in school. Due to the strong influence parents have on children's healthful behaviors particularly in younger years, it's imperative to examine the social cognitive impact parents have on this aspect of children's development. The objective of this study was to determine the impact parental self-efficacy and parental role responsibility have on child's nutritional, physical activity, and weight categories. Parents ( N = 820) responded to a questionnaire after participating in a child health screening project. Parental self-efficacy for assisting in their child's healthful behaviors has a strong association with the child's weight status, nutrition and physical activity. In order to make an effective change on child health behaviors, which lead to increased child academic test scores, these results suggest that school health interventionists and clinicians need to target basic psychological motivators of parental involvement.